Correction: Sriseubsai et al. Robust Design of PC/ABS Filled with Nano Carbon Black for Electromagnetic Shielding Effectiveness and Surface Resistivity. Processes 2020, 8, 616 - Wipoo Sriseubsai; Arsarin Tippayakraisorn; Jun Wei Lim (Processes, 2024)
With this correction, the Editorial Office together with the authors are making the following amendments to the published article [...]
Keywords: Electromagnetic wave absorption materials; Material Properties and Applications